Invisible City or the Search for the Best Guide to Klaipeda’s Culture - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2011)
The aim of this article is to find the best guide to Klaipeda’s culture. “Guide” means an appropriate narrative, which constructs urban and cultural identity. The main questions are to be answered: How Klaipeda’s culture changed from 1990 to 2010? What is the best representation of cultural transformations in post-soviet Klaipeda? What kinds of narratives are told on Klaipeda’s culture? Who are their authors? What is their content? Are those narratives commensurable? Is it possible to find the most appropriate guide to Klaipeda’s culture? Four narratives are investigated: narratives provided by historian, writer, philosopher and journalists (with the help of experts and vox populi). Those narratives about Klaipeda’s culture are deconstructed applying Italo Calvino’s metaphor of invisible cities, i.e. the cities that never existed, do not exist anymore or do not exist yet. These narratives instead of dealing with reality of current situation project an invisible city, which manifests as orientation towards past or future; fiction or abstraction; lost or projected etc. Different perspectives analyzed are incommensurable; therefore, these narratives present Klaipeda as an invisible city.